Implementasi Sistem Zonasi dalam Penerimaan Siswa Baru di Kecamatan Tellulimpoe Kabupaten Sinjai - Mursak, Mursak (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2023)
The division of the zone system in student admissions gets various responses from the community. The community thinks that the zone system can limit students' creativity in choosing schools that are of interest to students. The research method used is descriptive qualitative by conducting in-depth interviews with students, school principals and parents of students. The research findings are (1). The zone system carried out by the school is in accordance with the procedures and mechanisms implemented. (2). Lack of socialization from the Office of Occupation and Culture or the school so that parents can find out the division of school zones in each region.